Inequality in dental services: a scoping review on the role of access toward achieving universal health coverage in oral health - Arash Ghanbarzadegan; Madhan Balasubramanian; Liana Luzzi; David Brennan; Peivand Bastani (BMC, 2021)
Abstract Background Improving access to health services is a way towards achieving universal health coverage (UHC) in oral health. The purpose of this review was to map the determinants of access to dental services within a UHC framework. Method Scoping review methods were adopted for the review. PUBMED, Scopus, ISI Web of Science and ProQuest were searched for academic literature on determinants of access to dental services in OCED countries. Articles published in the last 20 years were included. No restriction was placed on study methods; only articles in English language were included. Qualitative synthesis was conducted, along with a trend analysis and mapping exercise. Result A total of 4320 articles were identified in the initial search; 57 articles were included in the qualitative synthesis. The results indicate 7 main themes as the determinants of access to dental services: family condition, cultural factors, health demands, affordability of services, availability of services, socio-environmental factors, geographical distance. Defined determinants of access to dental services, family condition, cultural factors and geographical access to dental services can fill the population axis of the UHC cube. Health demands and affordability of services fill the gap of financial protection as another axis of the UHC cube and finally, availability of dental services and socio-environmental factors are aligned with the appropriateness of services, the third axis of the UHC cube. Conclusion According to the results, family condition and cultural, health demands, affordability and availability of services, social environment, and geographic factors can affect dental health access and equality. Socio-cultural determinations also need to be considered in applied planning. Addressing these factors to improve access to dental services can pave the way for achieving universal health coverage in oral health and should be considered in different levels of policymaking.